A case of a mobile intrathoracic foreign object. (January 2020) - Eckersley, Martyn; Goncalves, Carla; Kumar, Dalip; Perera, Saman
Penetrating chest trauma to children is rare in the UK, making up 0.8% of wounds to children. When it does occur, it often results in damage to mediastinal structures including but not limited to the heart, lungs and great vessels. Rarely foreign objects can be intrapericardial. We present the case of a 14-year-old boy who presented haemodynamically stable following pellet gun wound to the chest. Multi-modality imaging revealed the bullet to be in the pericardium without associated cardiothoracic injuries, confirmed following surgery. Although a multi-modality imaging approach was used in diagnosing the precise location of the gun pellet, including imaging involving ionising radiation, we argue that early localisation can potentially be achieved with initial imaging and basic anatomical correlation, reducing the time to diagnosis. Using all the images available, including CT scout images, can assist in localisation and identifying important negatives.